Diagnostic and Management Strategies in Patients with Persistent Fetal Vasculature: Current Insights - Prakhunhungsit S (Dove Medical Press, 2020)
Supalert Prakhunhungsit,1 Audina M Berrocal2 1Department of Ophthalmology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Bascom Palmer Eye Institute, Miller School of Medicine, University of Miami, Miami, FL, USACorrespondence: Audina M BerrocalBascom Palmer Eye Institute, Miller School of Medicine, University of Miami, 900 Northwest 17th Street, Floor 1, Miami, FL 33136, USATel +1 305-326-6000Email aberrocal@med.miami.eduAbstract: Persistent fetal vasculature (PFV), previously known as persistent hyperplastic primary vitreous, is a developmental malformation of the eyes that is caused by a failure of the hyaloid vasculature to regress in utero. PFV has been reported for decades; however, our understanding of the pathophysiology/pathogenesis of PFV, and the diagnostic and treatment modalities for PFV have evolved over time, and these advancements have improved diagnosis, treatment, and outcomes. However and in spite of these advancements, the heterogeneity of this disease continues to make PFV a diagnostic challenge. Here, we review what is currently known about various important aspects of PFV to update and enhance the knowledge of ophthalmologists who encounter and manage PFV in clinical practice.Keywords: diagnostic and management strategies, persistent fetal vasculature, PFV, current insights